Molecular Docking Study of Bioactive Compounds from Curcuma aeruginosa Roxb. as Antioxidant and Anticancer Activities - Ambarsari, Laksmi; Nurjanah, Siti; Artika, I Made; Fatriani, Rizka (Tropical Biopharmaca Research Center, IPB University, 2023)
Cancer is one type of dangerous disease that is increasing every year. Free radicals are the cause of gene mutations (cancer). Cancer will develop uncontrollably due to the occurrence of the cell cycle and the presence of compounds that trigger cell proliferation and inhibit the process of apoptosis. This cancer treatment is carried out by giving cyclin-dependent kinase2 (CDK2) and cyclooxygenase-2 (COX-2) inhibitor drugs to inhibit cancer development, as well as lipoxygenase (LOX) inhibitor drugs for the formation of free radicals. Curcuma aeruginosa RoxB., the plant, is known to have the potential for antioxidant and anticancer properties. This study aims to determine the molecular interaction between the dominant compound in the ethanol extract of C. aeruginosa with CDK2, COX-2, and LOX receptors. The type of ligand interaction with the receptor was determined through the parameters of affinity energy (∆G), inhibition constant (Ki), type of interaction, and percentage of binding site similarity (%BSS). The results showed that the gajutsulacton A had the best potential in inhibiting CDK2. The cucumenol may be a COX-2 inhibitor, and there are no compounds that can inhibit LOX as well as an antioxidant. Thus, our findings demonstrate the potential for C. aeruginosa bioactive to serve as anticancer candidate molecules against CDK2 and COX-2 receptors.